The use of dermal automesh for incidental hernia repair in abdominoplasty: Clinical, biochemical, and radiological results - Özkaya Mutlu, Özay; Egemen, Onur; Akan, Arzu; Akan, Mithat; Karahangil, Mehmet; Filinte, Gaye; Bozdağ, Ergün; Sünbüloğlu, Emin; Kurtul, Hülya (Informa Healthcare, 2015)
Abdominal wall hernias are often diagnosed on clinical examination or encountered intraoperatively during an abdominoplasty. The aim of this study is to evaluate the long-term results of the use of dermal automesh for the repair of incidental hernias during abdominoplasty operations, and to perform a comparative analysis of the biomechanical strengths of dermal automesh vs biological tissue graft. Between 2008 - 2012, dermal automesh was used in 12 patients for hernia repair. After repair of hernia, dermal automesh was applied over the repaired area in an onlay fashion. Postoperative follow-up was performed by physical examination and magnetic resonance imaging (MRI) of the abdominal wall. Biomechanical test was performed with prepared samples from excised abdominal panniculus for tensile strength and yield power. Mean age was 45 years (range = 36 - 54 years). Total follow-up was 26 (14 - 52) months. MRI studies showed that there were no hernias or defects of the anterior abdominal wall. The tensile strength of the dermal mesh was measured as 15.9 +/- 6.0 Mpa (6.4 - 24.5), maximum load before yield measured 680 +/- 175.2 N (336.0 - 856.0). In conclusion, dermal automesh is a useful option for surgeons who encounter undiagnosed hernias during abdominoplasties.
WOS: 000354408600008
PubMed ID: 25384920
Keywords: Plastic Surgery; Abdominoplasty; Hernia Repair; Dermal Automesh